PEMBATALAN SERTIPIKAT HAK MILIK ATAS PERINTAH PUTUSAN PENGADILAN TATA USAHA NEGARA DIKARENAKAN CACAT ADMINISTRASI (STUDI KASUS PUTUSAN MAHKAMAH AGUNG No. 457 K/TUN/2013) - NONI WULANDARI LUBIS (PREMISE LAW JURNAL, 2017)
ABSTRACT Land registration is intended to compile and provide complete information about a plot of land and give legal certainty to the holders of land rights. The system of land registration in Indonesia is a negative system which has the positive tendency in placing land rights certificate as strong evidence although it is not absolute one since there will be the possibility for its holder to be claimed by other people who feel harmed by that certificate. The objective of this thesis is to analyze the dispute between Norma Tampubolon against the Land Office of Medan and Datuk Syahrial as the certificate holder that caused the Ownership Certificate No. 327/Sukaraja, registered in the name of Datuk Syahrial to be revoked due to its administrative defect through the Supreme Court’s Ruling No. 457 K/TUN/2013. This Ruling has encouraged the writer to find out the reason(s) of the State Administrative Court to pronounce the revocation of the certificate, the legal consequence on the revoked certificate, and the legal protection for its holder. The research used descriptive analytic and juridical normative method by analyzing the prevailing and competent legal provisions to be used as the basis for solving the research problems by using information from the source persons in supporting it. The result of the research showed that administrative defect became one of the reasons why the State Administrative Court pronounced an order to revoke the certificate. Since the Supreme Court’s Ruling No. 457 K/TUN/2013 was final and conclusive, the Ownership Certificate No. 327/Sukaraja was declared revoked and withdrawn from the circulation, and its status became the state land. Besides that, in reality, the Ruling did not give any legal certainty and legal protection to the certificate holder; on the other hand, it provided legal protection for the party that was won by the Court. Keywords: Land Registration, Revocation of Land Rights Certificate